Sipakatau, Sipakainge, Sipakalebbi, Siri Na Pace: A Multicultural Counseling Model in Terminating Moral Degradation - Izramadhani, Nur Suci; Bakhtiar, Muhammad Ilham; Ahmad Yusuf; Syaifullah Nur; Sutra Awaliyah; Sabil Husin (International Journal of Multicultural Counseling and Development, 2024)
This study discusses the development of a multicultural counseling model based on 4S cultural values to terminate moral degradation among adolescents which is one of the factors that cause various social problems. This study generally aims to present a multicultural counseling service guide for guidance and counseling teachers. The specific objectives of this study are: 1) To describe students' needs for a multicultural counseling model based on 4S cultural values "(sipakatau, sipakainge, sipakalebbi, siri na pacce)" in terminating moral degradation among them. 2) To describe the ideal multicultural counseling model based on 4S cultural values "(sipakatau, sipakainge, sipakalebbi, siri na pacce)" through a feasibility test, usability test, and accuracy test so that it can be applied to terminate moral degradation among students 3) To identify if there are differences before and after the implementation of multicultural counseling services based on 4S cultural values "(sipakatau, sipakainge, sipakalebbi, siri na pacce)". The study was carried out through a Research and Development approach from Borg & Gold. Data were analyzed qualitatively and quantitatively. Quantitative data from paired observations were analyzed using the Wilcoxon test to identify whether they were different or not. The Wilcoxon test using SPSS version 22 for Pre-Test and Post-Test data showed that students' moral awareness increased after participating in multicultural counseling activities based on 4S culture. The study is authentically reported by authors and has not been published in any journal.